2018
DOI: 10.1017/s2045796018000483
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autism Spectrum Disorder in a large Italian catchment area: a school-based population study within the ASDEU project

Abstract: This is the first population-based ASD prevalence study conducted in Italy so far and its results indicate a prevalence of ASD in children aged 7-9 years of about one in 87. This finding may help regional, national and international health planners to improve ASD policies for ASD children and their families in the public healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 64 publications
11
99
3
3
Order By: Relevance
“…In terms of caries severity, the average DMFT/dmft score for our sample (2.91) is substantially smaller than the one obtained in comparable studies conducted in Africa [24,27] (where average values of DMFT/dmft of 4.79 and 7.23 have been found), slightly smaller than the one reported in a similar study in Turkey [36] and slightly larger than those obtained in studies on autism in Asian populations [20,21,[36][37][38] (for which an average value between 2.01 and 2.4 has been reported). We found that both caries prevalence and caries severity have a statistically significant association with the type of diet and the periodontal indices PI and GI of the autistic patient but, contrary to the findings of similar studies [12,[36][37][38], a not statistically significant association with age and gender was found. No statistical association between autism severity (as measured by the Frankl scale rating) was found.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In terms of caries severity, the average DMFT/dmft score for our sample (2.91) is substantially smaller than the one obtained in comparable studies conducted in Africa [24,27] (where average values of DMFT/dmft of 4.79 and 7.23 have been found), slightly smaller than the one reported in a similar study in Turkey [36] and slightly larger than those obtained in studies on autism in Asian populations [20,21,[36][37][38] (for which an average value between 2.01 and 2.4 has been reported). We found that both caries prevalence and caries severity have a statistically significant association with the type of diet and the periodontal indices PI and GI of the autistic patient but, contrary to the findings of similar studies [12,[36][37][38], a not statistically significant association with age and gender was found. No statistical association between autism severity (as measured by the Frankl scale rating) was found.…”
Section: Discussioncontrasting
confidence: 99%
“…As far as Italy is concerned, prevalence rates estimated from local surveys on patients attended to by the National Health System (NHS) in Emilia-Romagna, Piemonte, and Toscana regions range from 15/10,000 to 80/10,000 [12].…”
Section: Introductionmentioning
confidence: 99%
“…As for ASD, current available prevalence estimates in Italy originate from local sources, namely two regional administrative registers and one single population-based study, performed in one Italian province (Pisa, ASDEU 2016, age 7-9 years, 11.5/1000; Narzisi et al 2018). Lacking an Italian national estimate of ASD prevalence, hardly we can assess the exact number of children and adolescents with ASD in need of services, which represents a limitation of the present study for the evaluation of CAMHs capacity to manage ASD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Autism spectrum disorders (ASDs) are neurodevelopmental conditions, affecting approximately 1% of children in Italy [1], and characterized by persistent deficits in social communication and interaction, along with the presence of restrictive and repetitive behaviors [2]. Eye tracking is a technique that is opening new avenues for quantitative, objective, simple, non-invasive evaluation of the visual patterns in young individuals with ASD [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A more advanced form of social attention is joint attention (JA), which is the ability to coordinate visual attention with another individual to an object or event that emerges between 6 and 12 months of age in typical development [10]. Two types of JA are described in the literature: (1) Response to joint attention (RJA), which is the ability to follow the direction of other's gaze; and (2) initiating joint attention (IJA), which is the ability to use gaze to direct the attention of others towards a shared object or event of interest [11]. JA impairment is consistently reported as one of the earliest and specific signs of ASD that becomes apparent at the end of the first year of life [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%